ANALYSIS OF PATIENT’S SATISFACTION WITH CLEAN INTERMITTENT URETHRAL CATHETERIZATION (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objectives: To compare and evaluate the aspects of the use of two bladder catheters for the person undergoing treatment with post-void residual, in clean intermittent bladder catheterization (CIL). Method: Quantitative, observational, and descriptive analysis developed in a reference outpatient clinic, for 48 municipalities, from September to November 2020. Fifty patients with post-void residual, who underwent CVIL, took part in the study. Their average age was 44,8 years old, and 72% of them were male. Two lubricated catheters were compared, from different technologies, both with attached bags, for seven days, six catheterizations a day, using a validated instrument of perception of customer satisfaction. Data were analyzed by the software Statistical Package for the Social Sciences (SPSS) Statistics 23.0, and for the comparison of the two catheters it was used the Wilcoxon’s non-parametric test. Results: The polyvinyl chloride (PVC) catheter pre-lubricated with glycerol reached greaterparticipant satisfaction in the evaluated attributes (90 versus 86%) in relation to the hydrophilic polyurethane (PVP) pre-lubricated catheter, although there was no statistical significance on the partial or total scores of the instrument used. Conclusion: The study allowed the comparison of two catheters, and the evaluation of the general score for both was positive. Some negative evaluation for certain attributes is possible to be improved. This kind of study is able to discriminate the catheters, and it can be reproduced.